A detailed analysis of the recurrence timing and pattern after curative surgery in patients undergoing neoadjuvant therapy or upfront surgery for gastric cancer. Issue 2 (29th April 2020) - Agnes, Annamaria; Biondi, Alberto; Laurino, Antonio; Strippoli, Antonia; Ricci, Riccardo; Pozzo, Carmelo; Persiani, Roberto; D'Ugo, Domenico
Abstract: Background and Objectives: The aim of this study was to determine whether the administration of neoadjuvant therapy (NAD) affects the incidence, timing, and pattern of recurrence in patients treated by curative gastrectomy. Methods: Sixty‐nine patients undergoing NAD and R0 gastrectomy were compared with 198 patients undergoing upfront surgery using the propensity score matching (PSM) method. Disease‐free survival (DFS), disease‐specific survival (DSS), and progression‐free survival (PFS) analyses were conducted with a log‐rank test and Cox regression. Risk factors for recurrence were assessed by logistic regression. Results: Among 69 patients with NAD, 28 (40.6%) experienced recurrence, and signet‐ring cell (SRC) carcinoma was the only factor independently associated with recurrence. In the whole sample, NAD did not influence DFS, DSS, rate of recurrence, or PFS. After PSM, the variables associated with DFS were cN1, type of gastrectomy, the presence of SRCs, and the presence of lymphovascular invasion. Variables independently associated with recurrence were cN1, type of gastrectomy, and the presence of SRCs. Conclusions: NAD had no impact on DFS, DSS, or the pattern of recurrence in any patients with gastric cancer. To define a better treatment strategy, future studies should focus on subtypes that do not respond to the current neoadjuvant regimens.